KONSELING INDIVIDUAL DENGAN PENDEKATAN PERSON-CENTERED THERAPY UNTUK MENINGKATKAN IDENTITAS DIRI - Gusti Rahayu; Mudjiran Mudjiran; Yeni Karneli (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Abstract: The formation of self-identity is essential because the task of development at that time is to adapt to the changes that are in him. If the formation of adolescent self-identity is disrupted it will result in the emergence of fear, uncertainty, tension, isolation, and inability to make decisions. The assistance that counselors can provide to improve adolescent self-identity is to provide individual counseling services using a person-centered therapy approach. The research method used in this study is descriptive qualitative with a literature study approach which describes in detail the significance of individual counseling with a person-centered therapy approach to improve self-identity.